O079 Predictive value for elevated platelet-derived SGPVI in venous in-stent stenosis in patients with post-thrombotic syndrome. (22nd July 2022) - Gwozdz, AM; Black, SA; Bye, AP; Gibbins, JM; Patel, AS; Modara, B; Smith, A; Saha, P
Abstract: Introduction: In-stent stenosis following intervention for post-thrombotic syndrome (PTS) occurs in ∼30% of cases, despite therapeutic anticoagulation. Our aim was to investigate whether platelets are involved. Methods: Blood was taken from case-matched patients before and after venous stenting. Flow-cytometry was used to assess platelet activation (P-selectin and/or phosphatidylserine exposure) while= functional activity was measured by plate-based aggregation and through a flow-cell model of thrombus formation. Soluble glycoprotein VI (sGPVI) was measured in plasma. Patients with in-stent stenosis requiring reintervention (>50% diameter reduction) were compared with those who did not. Results: Forty-five patients were recruited (median age: 43yrs (33–55yrs); 65% female), and 19/45 (42%) required reintervention (median time: 3wks (1day-3mths)). There was no difference in platelet activation or reactivity after stenting, but P-selectin exposure pre-stent was significantly higher in patients who developed in-stent stenosis (2.7%±0.4 vs 1.7%±0.2; P<0.05). Pre-stent sGPVI levels were increased in patients who developed in-stent stenosis (18.9±3.6ng/mL vs. 7.4±0.9ng/mL; P<0.01). Platelet reactivity to collagen-related peptide, a GPVI-specific platelet agonist, was reduced in patients who developed in-stent stenosis (logEC50 = -6.5M±0.3 vs -7.2M±0.2; P<0.05; n=33). Pre-stent platelet accumulation (26.6AU±0.5 vs 19.0AU±8.1; P=0.04) was significantly increased in PTS patients compared with healthy controls. Conclusion: Venous stenting does not activate platelets, but patients who developed in-stent stenosis exhibited greater levels of pre-stent platelet activation, greater loss of platelet surface GPVI in the form of sGPVI and reduction in reactivity to GPVI activation. sGPVI may have potential to risk stratify patients undergoing venous stenting and predict who requires closer surveillance. Take-home message: Soluble GPVI may have potential to risk-stratify patients undergoing deep venous reconstruction and predict who requires closer surveillance.